Epidemiological Analysis of Stunting Incidence in Toddlers - Hasanuddin Hasanuddin; St. Aminah Ali; Yermi Yermi; Sunanto Sunanto; Kasmiati Kasmiati (International Journal of Health Sciences, 2026)
Stunting is a chronic nutritional problem characterized by a toddler's length or height being below the standard for their age. This condition reflects long-term malnutrition and impacts physical growth, cognitive development, and future productivity. Indonesia remains a country with a high prevalence of stunting, requiring epidemiological analysis to understand its incidence patterns and risk factors. This study aims to analyze the incidence of stunting in toddlers based on aspects of person, place, and time, as well as related factors. The study used an observational analytical design with a cross-sectional approach. The study sample consisted of 100 toddlers selected using a purposive sampling technique. Data were collected through anthropometric measurements and questionnaires. Data analysis was performed using univariate and bivariate methods using the Chi- Square test. The results showed that the prevalence of stunting remains high and is related to factors such as toddler age, maternal education, maternal nutritional status, and feeding patterns. It was concluded that the incidence of stunting is influenced by various multidimensional factors, requiring sustainable cross-sectoral interventions.